Deterioration in ankle reflex is associated with a reduced estimated glomerular filtration rate in patients with type 2 diabetes: A retrospective observational cohort study - Taichi Muramatsu; Daisuke Yamamuro; Akifumi Kushiyama; Takako Kikuchi (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction We investigated the association between the ankle reflex and the estimated glomerular filtration rate (eGFR) in patients with type 2 diabetes. Materials and Methods This was a single‐center, retrospective, observational cohort study. A total of 1,387 patients who underwent an ankle reflex examination between January 2005 and December 2015 were included in the analysis for the primary outcome. The findings of the ankle reflex examination were classified into three groups: normal, decreased, or absent. The primary outcome was defined as the incidence of a 40% loss of eGFR from baseline. A survival time analysis using the Kaplan–Meier method and a regression analysis using a Cox proportional hazards model were conducted to evaluate the association between the ankle reflex test results and loss of eGFR. Results The ankle reflex test results were as follows: normal, n = 678 (48.9%); decreased, n = 270 (19.5%); and absent, n = 439 (31.6%) patients. The median follow‐up period was 5.6 years in the observational period. In the univariate regression analysis, decreased and absent ankle reflexes were significantly associated with loss of eGFR. Moreover, decreased ankle reflex (hazard ratio: 1.83, 95% confidence interval: 1.16–2.87) and absent ankle reflex (hazard ratio: 2.57, 95% confidence interval: 1.76–3.76) were independently associated with loss of eGFR after adjusting for prognostic risk factors. Conclusions Decreased and absent ankle reflexes are closely and independently associated with loss of eGFR in patients with type 2 diabetes.